Antiradical and Antimicrobial Activity of Thiosemicarbaside and 1,2,4-Triazole Derivatives of Hydroxybenzoic Acid - Satpaeva, Zh.B.; Shulgau, Z.T.; Akhmetova, S.B.; Nurkenov, O.A.; Fazylov, S.D.; Burkeev, M.Zh. (Russian Journal of Bioorganic Chemistry, 2020)
The antimicrobial and antioxidant activity of synthesized biologically active compounds have been evaluated in comparison with the standard antioxidant, ascorbic acid. The antioxidant activity of the compounds has been studied by their ability to interact with the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH ). The proposed test system has revealed the pronounced antiradical activity of 2-(2-hydroxybenzoyl)-Nphenylhydrazinecarbothioamide (1) (IC50(DPPH) = 15.5 μM) and 2-(4-hydroxybenzoyl)N-phenylhydrazinecarbothiamide (2) (IC50(DPPH) = 31.7 μM). A weak antibacterial activity of these compounds has been shown against gram-positive and gram-negative test strains.
Keywords: antioxidant; antiradical; antimicrobial activity; strain; free radical; thiosemicarbazide; 1,2,4-triazole; DPPH